2018
DOI: 10.1136/postgradmedj-2018-136056
|View full text |Cite
|
Sign up to set email alerts
|

Hot topics in Fabry disease

Abstract: Fabry disease is a rare inborn error of the enzyme α-galactosidase (α-Gal) and results in lysosomal substrate accumulation in tissues with a wide range of clinical presentations. The disease has attracted a lot of interest over the last years, in particular since enzyme replacement therapy (ERT) has become widely available in 2001. With rising awareness and rising numbers of (diagnosed) patients, physicians encounter new challenges. Over 900 α-Gal gene mutations are currently known, some with doubtful clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 66 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…Fabry disease is treatable 8. Enzyme replacement therapy likely changes the natural history and the new oral chaperone shows particular activity in the management of the cardiomyopathy associated with several late-onset missense mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Fabry disease is treatable 8. Enzyme replacement therapy likely changes the natural history and the new oral chaperone shows particular activity in the management of the cardiomyopathy associated with several late-onset missense mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing antibodies, which constitute an important issue around ERT, have been recently studied for their impact on clinical outcomes [8]. A Japanese study reported a correlation between antibody levels and lyso-Gb3 levels.…”
Section: Other Biomarkersmentioning
confidence: 99%
“…Lyso-Gb3 is the Gb3 degradation product; it is currently measured in the context of disease screening and diagnosis. In fact, it helps in determining the pathogenicity of a mutation [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The defect encoding the enzyme galactosidase A (GLA) is located in the region q21, 22 in the long arm of the X chromosome. To date, more than 900 mutations of the GLA gen have been detected (7), among them many of unclear significance (GUVS) (8).…”
Section: Introductionmentioning
confidence: 99%